FIESTA: An MR arthrography celebration of shoulder joint anatomy, variants, and their mimics. Issue 2 (19th March 2012) - Yu, D.; Turmezei, T.D.; Kerslake, R.W.
Abstract Magnetic resonance (MR) arthrography is currently the gold standard radiological investigation for shoulder joint instability. Not only does this investigation allow for identification of important disease processes, but the reduced slice thickness and increased in‐plane resolution allowed by the latest imaging sequences also gives excellent demonstration of shoulder joint internal anatomy. This article describes the technique of MR arthrography of the shoulder practiced at our institution, briefly outlining features of the FIESTA (fast imaging employing steady state acquisition) MR sequence employed, including its advantages and limitations. A pictorial review of shoulder MR arthrography performed with this technique is presented, concentrating on normal shoulder joint internal anatomy and anatomical variants that may mimic pathology. Clin. Anat., 2013. © 2012 Wiley Periodicals, Inc.